2020
DOI: 10.3904/kjim.2017.275
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized clinical study evaluating the efficacy and compliance of oral sulfate solution and 2-L ascorbic acid plus polyethylene glycol

Abstract: Background/Aims: Oral sulfate solution (OSS) is an emerging cleansing agent for bowel preparation. However, data comparing OSS to other conventional bowel preparations in Asian patients are limited. Therefore, the objective of this study was to compare the efficacy and tolerability of OSS to ascorbic acid plus polyethylene glycol (AA + PEG) in Asian patients. Methods: This was a prospective, randomized, parallel, investigator-blind study performed in two university hospitals in Korea. Bowel preparation efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…Similar to our study, a recent European multicentric study found that patient compliance with OSS administration was excellent regardless of administration (i.e., same-day or split-dose) and that the most frequent adverse symptoms for OSS were nausea and abdominal pain [35]. In another study, the same symptoms were significantly more frequent in the OSS group compared to the 2-L PEG/Asc group [25]. In contrast, Kim et al [21] described no differences in adverse events among patients receiving OSS or 2L-PEG/Asc.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar to our study, a recent European multicentric study found that patient compliance with OSS administration was excellent regardless of administration (i.e., same-day or split-dose) and that the most frequent adverse symptoms for OSS were nausea and abdominal pain [35]. In another study, the same symptoms were significantly more frequent in the OSS group compared to the 2-L PEG/Asc group [25]. In contrast, Kim et al [21] described no differences in adverse events among patients receiving OSS or 2L-PEG/Asc.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, 82% of patients accepted the split-dose regimen, which, according to previous studies, significantly improves the quality of bowel cleansing [23]. A recent study performed by Rostom et al [25] found that PEG was superior to MCSP via a split dose regimen (p=0.007) [24] while Kwon et al [25] demonstrated better efficiency of OSS than 2-L PEG/ Asc in an Asian population (p=0.06). Yoo et al [19] reported more frequent excellent preparation (BBPS > 8) in patients administered MCSP as compared to patients given 2-L PEG/ Asc (p=0.003).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The split-dose regimen has a higher patient acceptance because of the lower fluid intake required each day. A phase III trial conducted in the United States 10 and some South Korean studies 11,12 confirmed the noninferiority of OSS to PEG-ASC. OSS has also been used in Europe and certain Latin American territories.…”
Section: Introductionmentioning
confidence: 89%
“…10 10 Four studies had participants in both arms on a low-residue diet. [11][12][13][14] Two studies had different precolonoscopy diets for each arm (OSS arm had light breakfast followed by clears; PEG + Asc had normal breakfast followed by light lunch). 5 All studies recorded the frequency of patients reporting some combination of nausea, vomiting, abdominal pain, and abdominal bloating.…”
Section: Description Of Variation In Study Methodsmentioning
confidence: 99%